ASPEK YURIDIS PROSES MIGRASI REKENING NASABAH DALAM RANGKA ROLL OUT PADA BANK SYARIAH INDONESIA - Didi Sukardi (IAIN Syekh Nurjati Cirebon, 2022)
Bank Syariah Indonesia is the result of the merger of Bank Syariah Mandiri, BRISyariah, and BNISyariah with the spirit to encourage growth in the level of inclusion and Islamic financial literacy and to present the largest Islamic bank in Indonesia. The research method used is qualitative with a normative juridical approach. This field research is descriptive qualitative research with a normative juridical approach. Data were obtained through observation, interviews, and document analysis. The purpose of this study is to examine the process of account migration in order to roll out BSI's customers, and the juridical aspects. The result of the research shows that rollout is done through customer account migration. BSI uses the BSM’s system so legacy bank customers had to migrate accounts. Merger decision through various security considerations. a new legal relationship was born between BSI and customers from the legal event of the agreement, namely the change of savings books and ATMs based on Article 1338 of the Civil Code as the Sun Servanda Pacta Principle. The validity of the rollout is in accordance with Article 1320 of the Civil Code with the transfer.Keywords: Migration, Account, Customer, Roll Out, Bank Syariah Indonesia